1988
DOI: 10.1161/01.hyp.12.5.491
|View full text |Cite
|
Sign up to set email alerts
|

Arterial hypertension is associated with hypalgesia in humans.

Abstract: SUMMARY An association between increased blood pressure and hypalgesia has been reported in several studies in animals and in a few reports in humans. We investigated the relationship between hypertension and pain perception by comparing the response to graded electrical stimulation of the tooth pulp, which is thought to represent an exclusively nodceptive system. The test was performed with a commercial tooth pulp tester in a large series of subjects with borderline or established hypertension and in three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(70 citation statements)
references
References 28 publications
6
64
0
Order By: Relevance
“…36 Some studies also indicate that acute elevations in blood pressure during exercise are related to painless ischemia, and this has been attributed to decreased pain perception caused by baroreceptor stimulation. [37][38][39][40] Studies have shown that patients with microalbuminuria manifest greater evidence of cardiovascular risks and events when compared to patients with normal UAE. In a group of patients with essential hypertension, we previously observed that those patients who displayed an increase in UAE also Silent ischemia and microalbuminuria S Bianchi et al manifested an increased thickness of the carotid artery, a recognized marker of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…36 Some studies also indicate that acute elevations in blood pressure during exercise are related to painless ischemia, and this has been attributed to decreased pain perception caused by baroreceptor stimulation. [37][38][39][40] Studies have shown that patients with microalbuminuria manifest greater evidence of cardiovascular risks and events when compared to patients with normal UAE. In a group of patients with essential hypertension, we previously observed that those patients who displayed an increase in UAE also Silent ischemia and microalbuminuria S Bianchi et al manifested an increased thickness of the carotid artery, a recognized marker of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hypoalgesia can extend into the normotensive blood pressure range in young adults at increased risk for hypertension, such as those with a parental history of hypertension, elevated resting blood pressure, or exaggerated cardiovascular reactivity to stress (Campbell and Ditto, 2002;France, 1999), although there are exceptions (al'Absi et al, 2000;Ghione et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ghione et al (1988) found no significant effect of age or gender on experimentally induced pain.…”
mentioning
confidence: 91%
“…Recently, several animal studies and a few human studies have demonstrated an association between increasea blood pressure (BP) and hypalgesia (a diminished perception of pain) (Ghione, Rosa, Mezzasalma, & Panattoni, 1988;Sheps et al, 1989). Ghione et al (1988) compared the perception of experimental dental pain between 80 normotensive subjects and 76 subjects with borderline or established hypertension on a blind basis for two and one-half years.…”
mentioning
confidence: 99%
See 1 more Smart Citation